Changes in Stoichiometry, Cellular RNA, and Alkaline Phosphatase Activity of Chlamydomonas in Response to Temperature and Nutrients - Hessen, Dag O.; Hafslund, Ola T.; Andersen, Tom; Broch, Catharina; Shala, Nita K.; Wojewodzic, Marcin W. (Frontiers in Microbiology, 2017)
Phytoplankton may respond both to elevated temperatures and reduced nutrients by changing their cellular stoichiometry and cell sizes. Since increased temperatures often cause increased thermal stratification and reduced vertical flux of nutrients into the mixed zone, it is difficult to disentangle these drivers in nature. In this study we used a factorial design with high and low levels of phosphorus (P) and high and low temperature to assess responses in cellular stoichiometry, levels of RNA, and alkaline phosphatase activity (APA) in the chlorophyte Chlamydomonas reinhardtii. Growth rate, C:P, C:N, N:P, RNA and APA all responded primarily to P treatment, but except for N:P and APA, also temperature contributed significantly. For RNA the contribution from temperature was particularly strong with higher cellular levels of RNA at low temperatures, suggesting a compensatory allocation to ribosomes at low temperature to maintain protein synthesis and growth. These experiments suggest that although P-limitation is the major determinant of growth rate and cellular stoichiometry, there are pronounced effects of temperature also via interaction with P. At the ecosystem level, nutrients and temperature will thus interact, but temperatures would likely exert a stronger impact on these phytoplankton traits indirectly via its force on stratification regimes and vertical nutrient fluxes.